A Symbiotic Organisms Search Algorithm for Blood Assignment Problem - Govender, Prinolan; Ezugwu, Absalom E. (Hybrid Metaheuristics, 2019)
The demand for blood transfusion is considered a real world problem which is needed for various medical emergencies. The blood assignment problem was introduced to address this problem. The formulation of this problem stretches from managing critical blood shortage levels and blood unit expiration, to blood compatibility between donor and patients. Another contributing factor to the blood assignment problem, lies in the blood bank having to import additional blood units from external sources when supply cannot meet the demand. These challenges have serious consequences especially in the case where the demand for blood is very high. Taking these factors into consideration, this study implements a metaheuristic hybrid algorithm that combines symbiotic organisms search algorithm with the blood assignment policy in relation to the blood banks of South Africa. The aim of this study is to minimize blood product wastage with regards to expiration and importation, whilst maximizing product delivery to patients in need. In addition, this study also implements a unique way of generating randomized datasets based on social events relating to South Africa public holidays. The computational results indicate that the proposed hybrid algorithm performed well in minimizing blood importation, and experienced no form of expiration throughout the time period.